Hubungan Kebahagiaan dengan Motivasi Belajar Matematika Kelas V SDN 17 Pekanbaru - Sindi Antika; Zetra Hainul Putra; Intan Kartika Sari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Happiness and motivation to learn mathematics are a must for students. With happiness in a student, it can create a sense of pleasure when doing something and motivation to learn mathematics needs to be in the student as well, with motivation or encouragement, learning will be more enthusiastic and enthusiastic, especially in learning mathematics. The purpose of this study was to see the correlation between happiness and motivation to learn mathematics in class V SDN 17 Pekanbaru. This study is a quantitative study with a correlational method and a population of 114 and a sample of 55 people. The results of the study showed a relationship between the two variables with a significance of 0.000 and a Pearson correlation value of 0.760 and a contribution from the variable of 58%, which means that happiness has a contribution of 58% to motivation to learn mathematics and the remaining 42% is influenced by other factors. This study is expected to provide the best solution that educators can do when teaching mathematics in the classroom.